2018
DOI: 10.21037/jtd.2018.01.14
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and influencing factors of coal miners in Xuzhou, China

et al.

Abstract: QOL of coal miners has been affected. Some measures might be taken by enterprise and coal miners themselves to protect the health of coal miners and improve their quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 27 publications
1
21
0
2
Order By: Relevance
“…Additionally, we stratified the association analyses by gender, age, and workplace, respectively, to derive more complete results specific to different subgroups. This study contributes to the previous researches which didn’t draw any conclusion about the relationship of sleep quality with job burnout among coal mine workers 13,14 , and provides a broader empirical basis for the relevant research on the mental health of coal miners.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Additionally, we stratified the association analyses by gender, age, and workplace, respectively, to derive more complete results specific to different subgroups. This study contributes to the previous researches which didn’t draw any conclusion about the relationship of sleep quality with job burnout among coal mine workers 13,14 , and provides a broader empirical basis for the relevant research on the mental health of coal miners.…”
Section: Introductionmentioning
confidence: 76%
“…It is not difficult to realize that the association of sleep status and job burnout differed among various kinds of workers. Different studies have been carried out on coal miners, but there has been no research specifically investigated the association of sleep and job burnout on this field of work 13,14 . So it is necessary to confirm the existence and magnitude of the potential relationship in this population for the consideration of occupational health.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Stress is a significant part of the living conditions of coal miners, correlating with harsh working conditions, including repetitive activities, lifting heavy materials, shift work and night work. 8 Besides, job burn-out results from working stress, and inappropriate work environment can trigger depression. 9 In addition, a study revealed average rates of 18.6%, 26.4% and 23.5% for hypertension, hyperlipidaemia and hyperglycaemic, respectively, in coal miners.…”
Section: Introductionmentioning
confidence: 99%
“…QoL is a multidimensional concept comprised of physical component summary (PCS) and mental component summary (MCS). It is included in widelyused health surveys, as an end point in medical care (Han et al, 2018).…”
Section: Introductionmentioning
confidence: 99%